Enhanced plasma miR-142-5p promotes the progression of intrahepatic cholangiocarcinoma via targeting PTEN - Wei, Guifen (Exp Ther Med, 2019)
The aim of the present study was to evaluate the expression and specific role of microRNA (miR)-142-5p in the progression of intrahepatic cholangiocarcinoma (ICC). Reverse transcription-quantitative polymerase chain reaction was performed to evaluate miR-142-5p expression in patients with ICC and healthy control subjects. The results revealed that plasma miR-142-5p was significantly increased in patients with ICC compared with the control group. Furthermore, miR-142-5p was also increased in ICC tissues compared with adjacent non-neoplastic tissues. Compared with patients with Ta-T1 stage ICC, miR-142-5p was significantly elevated in patients with ICC ≥T2 stage. Patients with ICC at G3 stage had much higher plasma miR-142-5p levels compared with those at G1/2 stage. Receiver operating characteristic analysis indicated that miR-142-5p could be used as a biomarker to differentiate patients with ICC from healthy controls. Kaplan-Meier analysis demonstrated that plasma miR-142-5p was negatively correlated with survival in patients with ICC. A dual luciferase reporter assay indicated that miR-142-5p significantly suppressed the relative luciferase activity of pmirGLO-PTEN-3′ untranslated region compared with the control group. In summary, the results of the present study provide novel data indicating that plasma miR-142-5p is significantly upregulated in patients with ICC. miR-142-5p may therefore have potential as a biomarker for screening patients with ICC from healthy controls.